2023
DOI: 10.1093/eurheartj/ehad109
|View full text |Cite|
|
Sign up to set email alerts
|

Participation in a clinical trial is associated with lower mortality but not lower risk of HF hospitalization in patients with heart failure: observations from the ESC EORP Heart Failure Long-Term Registry

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
1
16
1
Order By: Relevance
“…Kapelios et al . reported that an increase in loop diuretic doses compared with no change was associated with higher risk of HF death after index visit, whereas a decrease in loop diuretic doses compared with no change showed a trend of lower HF and cardiovascular deaths after index visit in outpatients with chronic HF 16 . Furthermore, novel effective, safe pharmacologic, and established methods to achieve decongestion without inducing end‐organ damage are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kapelios et al . reported that an increase in loop diuretic doses compared with no change was associated with higher risk of HF death after index visit, whereas a decrease in loop diuretic doses compared with no change showed a trend of lower HF and cardiovascular deaths after index visit in outpatients with chronic HF 16 . Furthermore, novel effective, safe pharmacologic, and established methods to achieve decongestion without inducing end‐organ damage are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of loop diuretics was calculated as a furosemide equivalent for patients who had received loop diuretics other than furosemide. The formula used to convert other loop diuretics to furosemide equivalents was as follows: furosemide 20 mg = azosemide 30 mg = torasemide 10 mg. 15,16 Changes in the dose of loop diuretics during hospitalization were calculated by comparing the dose at discharge with the dose at admission. Anaemia was defined using the World Health Organization criteria (haemoglobin of <12.0 g/dL in women and <13.0 g/dL in men).…”
Section: Data Collection and Definitionsmentioning
confidence: 99%
“…Complete decongestion while carefully monitoring renal function and electrolytes, is the target 9,61,97 . Several studies showed that high doses of loop diuretic are associated with an increased risk of mortality, even after multivariate adjustment or propensity matching 9,68,69,98,99 . Potential bias remains as sicker patients are more likely to receive higher doses of loop diuretics.…”
Section: Pre‐discharge Optimization Of Treatmentmentioning
confidence: 99%
“…Over the last years, the development of new drugs has revolutionized the treatment of HF, especially in those who suffer HF with reduced ejection fraction (HFrEF) 1,2 . However, there are several, worrisome signals indicating that newer therapies do not always reach the target population for many reasons 3–5 . Specifically, out‐of‐pocket cost, medical inertia or drug intolerance/side‐effects are some of them.…”
Section: Figurementioning
confidence: 99%
“…1,2 However, there are several, worrisome signals indicating that newer therapies do not always reach the target population for many reasons. [3][4][5] Specifically, out-of-pocket cost, medical inertia or drug intolerance/side-effects are some of them. How can we overcome these barriers?…”
mentioning
confidence: 99%